PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI ANALISIS MANAJEMEN RISIKO DI CAFE KOPI JELITA KOTA SERANG - Salapudin, Salapudin; Lesmana, Ihwan Satria (Yayasan Education and Social Center, 2023)
Human resources are a crucial element that every company must have. To support the smooth operation of the company, management efforts are needed so that the existing system can be well organized in accordance with the company's goals. This research aims to analyze improving human resource performance through the application of risk management analysis at Cafe Kopi Jelita, Serang City. This research adopts a qualitative approach method with a descriptive research type, utilizing direct interview techniques with managers and direct observation at the location. A qualitative approach and descriptive research were chosen to describe and understand more deeply the context and practices of risk management. Through direct interviews, researchers can interact directly with managers, obtaining contextual information about risk management strategies. Direct on-site observation provides an additional advantage, allowing researchers to dive into the realities of risk management practices directly, providing clearer insight into the implementation of theoretical concepts in real contexts. Using this approach, the research integrates risk management principles to develop strategies that can increase the effectiveness and efficiency of human resource management in the cafe. It is hoped that the results of this research will provide an in-depth view of how risk management analysis can be a valuable tool in improving human resource performance in the context of the cafe industry. The implications of these findings can provide practical guidance for business owners, managers and researchers who are interested in improving human resource management practices amidst the dynamics of the coffee industry